The Moderating Role of Leader-Member Exchange in the Relationships Between Emotional Labor and Burnout in Clinical Nurses - Eun Kyung Lee, PhD, RN; Eun Joo Ji, PhD, RN (Elsevier, 2018)
Purpose: This study aimed to identify the moderating effect of leader-member exchange in the relationship between emotional labor and burnout among clinical nurses. Methods: A cross-sectional study design was used. Participants were 170 registered nurses working in the general wards of two tertiary hospitals in Seoul, South Korea. The data were collected through convenience sampling using self-report measures of emotional labor, leader-member exchange, and burnout. The data were analyzed using hierarchical multiple regression. Results: Data from 165 nurses (response rate 97.1%) were utilized. The mean age of the participants was 28.42 years (SD = 5.43), and their mean years of experience as a nurse was 5.80 years (SD = 5.51). First, emotional modulation efforts in their profession and patient-focused emotional suppression (both factors of emotional labor) showed significant negative and positive effects, respectively, on burnout. Second, leader-member exchange showed a significant negative effect on burnout. Finally, when controlling for marital status and work unit, leader-member exchange had a moderating effect on the relationship between burnout and the two aforementioned factors of emotional labor. Conclusion: The results of this study suggest that as a way to reduce burnout, institutional support to enhance leader-member exchange should be established for nurses who are experiencing emotional labor. Keywords: burnout, emotional labor, leadership, nurse